2015
DOI: 10.14202/vetworld.2015.72-75
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence studies on animal chlamydiosis amongst ruminants in five states of India

Abstract: Background and Aim:Animal chlamydiosis, caused by different chlamydial species, is characterized by clinical or subclinical disease manifestations in cattle, buffalo, ovine, caprine and wild animal species. Animal chlamydiosis often remains underdiagnosed or undiagnosed, and its status in many parts of India is still unknown. Hence, the present study was conducted to determine the seroprevalence of animal chlamydiosis amongst ruminant livestock species of five states of India.Materials and Methods:Totally, 212… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Chlamydia seroprevalence has been reported in sheep and goats worldwide. For example, 10.60% seroprevalence has been reported in sheep in India (21), and 33% seroprevalence has been reported in Spain (22). The different seroprevalences in different counties in our study is probably attributed to the differences in sanitation, husbandry practices, and animal welfare.…”
Section: Discussionmentioning
confidence: 54%
“…Chlamydia seroprevalence has been reported in sheep and goats worldwide. For example, 10.60% seroprevalence has been reported in sheep in India (21), and 33% seroprevalence has been reported in Spain (22). The different seroprevalences in different counties in our study is probably attributed to the differences in sanitation, husbandry practices, and animal welfare.…”
Section: Discussionmentioning
confidence: 54%
“…2.17% (total sample=92) in Nawalpur and Chitwan District. Seroprevalence of Chlamydia abortus in ruminants varies widely from one country to another, 0.82% in Iraq (Majed et al, 2018), 4.75% in Ireland (Wilson et al, 2012) and 4.65% in five states of India (Chahota et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…C. abortus is endemic in ruminants throughout the world (Li et al, 2015) and it causes epizootic bovine abortion in cattle (Gokce et al, 2007). This bacterium causes abortion, infertility, weak calves, fetal loss, and mastitis in cattle and also in sheep and goat (Chahota et al, 2015). Animals can become infected at any time of the year, especially via the ingestion of elemental bodies from an aborted fetus, placentas, and uterine discharge from infected individuals that contaminate drinking water or food (Longbottom and Coulter, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bhardwaj et al ( 2017 ) conducted a study, and they reported that only a few strains of C. psittaci are circulating in the region of Himachal Pradesh and apart from the respiratory problems, C. psittaci causes reproductive issues also in the livestock population. Sero assays conducted by antigens developed from the local strain of C. psittaci concluded that chlamydial infections are endemic amongst ruminants in five states (Himachal Pradesh, Punjab, Andhra Pradesh, Maharashtra, Jammu and Kashmir) of India, which may represent one of the causes of pneumonia, abortion, arthritis, enteritis, and other clinical outcomes (Chahota et al 2015 ). Interestingly, C. psittaci has been isolated from the cervidae family in tissues and faeces samples in the North-Western Himalayan region (Rattan et al 2005 ).…”
Section: Indian Perspectivementioning
confidence: 99%